The challenges and potential for increasing the recycling of post-consumer aluminium scrap in the UK - Liu, Milan; Schneider, Kilian; Litos, Lampros; Salonitis, Konstantinos (Springer, 2025)
With the emphasis on circular economy and sustainable development, the demand for the reuse of post-consumer aluminium (Al) scrap is rising. Current recycling processes, such as downgrading and dilution, can lead to the accumulation of contaminants in the resulting alloy and a surplus of non-recyclable scrap. This is not viable for sustainable development of the manufacturing industry, and optimised recycling strategies and systems are required. The existing literature is relatively scattered and lacks a unified integration of related fields. This paper is trying to mitigate the gap by a cohesive synthesis across interconnected domains. It aims to analyse the potential problems and barriers to the upgrading of the aluminium scrap recycling industry in the United Kingdom(UK) and explore feasible solutions from different perspectives. This article reviews the latest literature while also collecting recent information from the industry to analyse the overall development bottlenecks of aluminium recycling and reuse development. These obstacles include a dearth of available data, the complexity of diverse alloy types, mismatches between market supply and demand, and associated recycling costs. It points out potentially effective actions through use cases and provides a framework for improving strategies and future work.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 12 Responsible Consumption and Production